2021
DOI: 10.18517/ijaseit.11.4.14034
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of Emotion in Indian Classical Dance Using EMG Signal

Abstract: Indian classical dance forms like Kathak are an enrichment of Indian culture and tradition. These dance forms glorify its beauty by expressing nine emotions (Navras) such as Adbhut (amazed), Bhayanaka (fearful), Hasya (humorous), Karuna (tragic), Raudra (fierce), Shringar (loving smile), Veer (heroic), Bibhatsa (disgusted), and Shant (peaceful). Identifying correct emotions is an important task. The objective of this research work is to recognize Navras in the Kathak dance. Proposed research work can assist da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Emotional recognition by facial expression can work accurately most of the time under normal lighting conditions with frontal face position [31]. From the face images cropped by the face detection algorithm in Figure 5, it is observed that the employee is currently happy and the result generated was also correct.…”
Section: ) Convolutional Neural Network (Cnn)mentioning
confidence: 99%
“…Emotional recognition by facial expression can work accurately most of the time under normal lighting conditions with frontal face position [31]. From the face images cropped by the face detection algorithm in Figure 5, it is observed that the employee is currently happy and the result generated was also correct.…”
Section: ) Convolutional Neural Network (Cnn)mentioning
confidence: 99%